Stereospecific Biotransformation of Dihydrodaidzein into (3S)-Equol by the Human Intestinal Bacterium Eggerthella Strain Julong 732 - Kim, Mihyang; Kim, Su-Il; Han, Jaehong; Wang, Xiu-Ling; Song, Dae-Geun; Kim, Soo-Un (AMER SOC MICROBIOLOGY, 2009)
Stereochemical course of isoflavanone dihydrodaidzein (DHD) reduction into the isoflavan (3S)-equol via tetrahydrodaidzein (THD) by the human intestinal anaerobic bacterium Eggerthella strain Julong 732 was studied. THD was synthesized by catalytic hydrogenation, and each stereoisomer was separated by chiral high-performance liquid chromatography. Circular dichroism spectroscopy was used to elucidate the absolute configurations of four synthetic THD stereoisomers. Rapid racemization of DHD catalyzed by Julong 732 prevented the substrate stereospecificity in the conversion of DHD into THD from being confirmed. The absolute configuration of THD, prepared by reduction of DHD in the cell-free incubation, was assigned as (3R, 4S) via comparison of the retention time to that of the authentic THD by chiral chromatography. Dehydroequol (DE) was unable to produce the (3S)-equol both in the cell-free reaction and in the bacterial transformation, negating the possible intermediacy of DE. Finally, the intermediate (3R,4S)-THD was reduced into (3S)-equol by the whole cell, indicating the inversion of stereochemistry at C-3 during the reduction. A possible mechanism accounting for the racemization of DHD and the inversion of configuration of THD during reduction into (3S)-equol is proposed.
Keywords: EQUOL-PRODUCING BACTERIUM; HUMAN FECES; ISOFLAVONE METABOLITES; ABSOLUTE-CONFIGURATIONS; ANAEROBIC BACTERIUM; SOY ISOFLAVONES; DAIDZEIN; IDENTIFICATION; GENISTEIN; DIHYDROGENISTEIN